Oligo-Carrageenan Kappa and Oligo-Ulvans Stimulate Growth in Arabidopsis Thaliana by Increasing the Expression of Proteins Involved in Primary Metabolism, Phytohormones Synthesis and Cell Division - Moenne-Munoz, A; Gonzalez-Figueroa, A; Maldonado-Soto, J (Springer Science and Business Media B.V., 2025)
Carrageenan kappa (CK), a polysaccharide obtained from marine red algae, oligo-carragenan kappa (OCK), an oligosaccharide obtained by acid hydrolysis of CK, and oligo-ulvans (OU), an oligosaccharide obtained by acid hydrolysis of ulvans from marine green algae, were sprayed on leaves of Arabidopsis thaliana at a concentration of 1 mg mL− 1, five times, every two days, and plants were cultivated for ten additional days. Plants treated with water (control) or with an aqueous solution of CK, OCK and OU showed an increase in fresh weight (FW) and dry weight (DW), mainly in those treated with OCK and OU. Plants treated with OCK and OU showed an increase in rosette diameter and length of the primary root, but not those treated with CK. Plants treated with OCK and OU showed an increase in the level of transcripts encoding enzymes such as rubisco, glutamine synthase and O-acetyl thiol lyase, but not those treated with CK. Plants treated with CK, OCK and OU showed an increase in transcripts encoding an enzyme involved in gibberellin A3 synthesis whereas plants treated with OCK and OU showed increased transcript encoding an enzyme involved in epi-brassinolide synthesis, but not those treated with CK. Plants treated with OCK and OU showed increased transcripts encoding cyclin A, cyclin D and CDPKB, which regulate the cell cycle, but not those treated with CK. Plants treated with OCK and OU showed an increase in the number of cells per leaf area and in the content of total proteins. Thus, OCK and OU better stimulate growth of A. thaliana compared to CK by increasing the expression of genes involved in primary metabolism, phytohormone synthesis and cell division and act on different cellular pathways compared with CK. Therefore, these oligosaccharides can be useful for biotechnological purposes by increasing plant growth and productivity. © The Author(s), under exclusive licence to Springer Nature B.V. 2025.